1972
DOI: 10.1677/joe.0.0550105
|View full text |Cite
|
Sign up to set email alerts
|

The METABOLIC CLEARANCE RATE AND PRODUCTION RATE OF PROGESTERONE AND THE CONVERSION OF PROGESTERONE TO 20α-Hydroxypregn-4-en-3-One IN THE SHEEP

Abstract: SUMMARY Tracer kinetic techniques were used to determine the metabolic clearance rate (MCR) and production rate (PR) of progesterone in the sheep during pregnancy, the oestrous cycle and the lactation anoestrus. The MCR from whole blood measured by the continuous infusion of [3H]progesterone was 3·483 ± 0·126 l/min in pregnancy, 2·752 ± 0·239 l/min in the oestrous cycle and 5·020 ± 0·566 l/min in lactation anoestrus. After correcting for body weight the respective values were 0·077, 0·077 and 0·133 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0
2

Year Published

1975
1975
2008
2008

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 0 publications
4
52
0
2
Order By: Relevance
“…This may not, however, reflect abnormal progesterone production since the results could be explained by the fact that anoestrous ewes have a somewhat higher metabolic clearance rate for progesterone than do cyclic animals (Bedford, Harrison & Heap, 1972). In Ewe 0_ (Text-fig.…”
Section: Discussionmentioning
confidence: 97%
“…This may not, however, reflect abnormal progesterone production since the results could be explained by the fact that anoestrous ewes have a somewhat higher metabolic clearance rate for progesterone than do cyclic animals (Bedford, Harrison & Heap, 1972). In Ewe 0_ (Text-fig.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, we believe the decreased cytochrome P450 2C and 3A activities in the sodium propionate-supplemented animals compared to the sodium acetate-supplemented animals are most likely due to the effect of elevated insulin concentrations at the time of biopsy. Bedford et al (1972 and1974) reported metabolic clearance rates (volume of blood cleared of progesterone per unit time) for progesterone to be approximately 3.5 to 4.3 l/min in sheep. Splanchnic clearance rate of progesterone could account for 30% of total progesterone metabolism, and 70% to 90% of the total clearance of progesterone in these splanchnic organs was cleared by the liver (Bedford et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…It seems improbable that PGF-2a stimulated myometrial contractions in our preparations in view of the large amount of fluid that accumulated in the uterus, but the effect may have been inhibited by the circulating level of progesterone normally found in pregnancy (Bedford, Harrison & Heap, 1972).…”
Section: Discussionmentioning
confidence: 84%